Effects of different glucose concentration on separate hydrolysis and fermentation (SHF) of selected food waste for biothanol production - Fatin Shafiqa, Md Shah (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The fermentation was carried out by using the hydrolysed food waste as a glucose source and Saccharomyces cerevisiae as a microorganism in order to produce ethanol. »X3;31 ?t Aj hop /b / >G78• %18 7- ;13X• [~7· • X+?· 1;3G1 ? x? ~7 ?838 7[ [77 %18;• which was conducted at 55°C, pH 5.0 for 24 hours. The effects of high glucose concentration on ethanol concentration were investigated in this study. The glucose obtained from hydrolysed food waste of 10 g/1, 20 g/1 and 50 g/1 were used as a substrate in this study. Temperature at 30°C, pH 5.0 and agitation rate of 100 rpm was used as a control throughout the fermentation. The glucose consumption in all fermentation was not different significantly whereas the highest ethanol production, (26.57 g/1) was achieved by using 50 g/1 of glucose concentration. Therefore, the optimum glucose concentration for the highest ethanol production was 50 g/1.